Composition, isolation, identification and function of adipose tissue-derived exosomes - Rui Zhao (Taylor & Francis Group, 2021)
Exosomes are nano-sized extracellular vesicles (30–160 nm diameter) with lipid bilayer membrane secrete by various cells that mediate the communication between cells and tissue, which contain a variety of non-coding RNAs, mRNAs, proteins, lipids and other functional substances. Adipose tissue is important energy storage and endocrine organ in the organism. Recent studies have revealed that adipose tissue-derived exosomes (AT-Exosomes) play a critical role in many physiologically and pathologically functions. Physiologically, AT-Exosomes could regulate the metabolic homoeostasis of various organs or cells including liver and skeletal muscle. Pathologically, they could be used in the treatment of disease and or that they may be involved in the progression of the disease. In this review, we describe the basic principles and methods of exosomes isolation and identification, as well as further summary the specific methods. Moreover, we categorize the relevant studies of AT-Exosomes and summarize the different components and biological functions of mammalian exosomes. Most importantly, we elaborate AT-Exosomes crosstalk within adipose tissue and their functions on other tissues or organs from the physiological and pathological perspective. Based on the above analysis, we discuss what remains to be discovered problems in AT-Exosomes studies and prospect their directions needed to be further explored in the future.